A comparative study of the effective response of di-potassium phosphate (K2HPO4) on physiological, biochemical and anatomical aspects of crops dwelling with zinc oxide nanoparticles toxicity. Issue 2 (8th March 2021) - Yadav, Vaishali; Arif, Namira; Chauhan, Devendra Kumar
Abstract: The dipotassium phosphate (K2 HPO4 ) is a source of phosphorus (P), which is an essential micronutrient for plant growth and reproduction and also acts as a stress alleviator against abiotic stresses. Therefore, it could also become a potential mineral to cope up with zinc oxide nanoparticles' (ZnONPs) toxicity in crops. This study primarily includes synthesis, characterization and differential toxic impacts of ZnONPs on two crop plantsThis study includes synthesis, characterization and differential toxic impacts of ZnONPs on two crop plants, i.e. Triticum aestivum and Solanum lycopersicum, as well as assuage the toxic impacts of ZnONPs through nutrient management approach implied via supplementation of P. The growth and physiological changes under toxic doses of ZnONPs and ameliorative potential of P in crop plants were examined by analysing growth, intracellular Zn accumulation, photosynthetic pigment contents, the kinetics of photosystem II (PS II) photochemistry, root cell anatomy and cell viability via histochemical staining 4′, 6-diamidino-2-phenylindole and propidium iodide. ZnONPs at 500 and 1000 μM concentrations significantly affected the growth, photosynthetic pigment and PS II photochemistry and cell death in both the plants. It also caused deformation in root anatomy of T. aestivum and S. lycopersicum . Whereas supplementation of P caused significant improvement against ZnONPs stress by causing remarkable enhancement in growth, photosynthetic pigments and activity of PS II photochemistry and decreased cell death. Moreover, the study also discloses the tolerant nature of S. lycopersicum comparing with T. aestivum seedlings. Thus, P is comparatively more effective in managing the ZnONPs toxicity in S. lycopersicum than in T. aestivum . Graphical Abstract: